2011
DOI: 10.1093/hmg/ddr325
|View full text |Cite
|
Sign up to set email alerts
|

Common variants at VRK2 and TCF4 conferring risk of schizophrenia

Abstract: Common sequence variants have recently joined rare structural polymorphisms as genetic factors with strong evidence for association with schizophrenia. Here we extend our previous genome-wide association study and meta-analysis (totalling 7 946 cases and 19 036 controls) by examining an expanded set of variants using an enlarged follow-up sample (up to 10 260 cases and 23 500 controls). In addition to previously reported alleles in the major histocompatibility complex region, near neurogranin (NRGN) and in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
166
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(175 citation statements)
references
References 28 publications
5
166
1
3
Order By: Relevance
“…These two SNPs showed nominally significant associations among the replication samples (rs2709370 Supplementary Table S5. The odds ratios in the cumulative analysis are comparable with other genes reported as significantly associated with psychiatric disorders in larger meta-analyses 59,60 and exceed the Venice interim criteria for 'small summary' findings. 61 Taken collectively, the association analysis suggests that SNPs in CREB1 may confer risk of BD among Europeans.…”
Section: Creb1 Variants Confer Risk Of Bdsupporting
confidence: 67%
“…These two SNPs showed nominally significant associations among the replication samples (rs2709370 Supplementary Table S5. The odds ratios in the cumulative analysis are comparable with other genes reported as significantly associated with psychiatric disorders in larger meta-analyses 59,60 and exceed the Venice interim criteria for 'small summary' findings. 61 Taken collectively, the association analysis suggests that SNPs in CREB1 may confer risk of BD among Europeans.…”
Section: Creb1 Variants Confer Risk Of Bdsupporting
confidence: 67%
“…Family, twin and adoption studies have revealed a strong genetic component with estimates of heritability about 80%. 1 So far, numerous molecular genetic studies on schizophrenia have been performed, and many susceptibility genes have been identified through linkage analyses, 2,3 candidate gene association studies, 4,5 genome-wide association studies (GWAS) [6][7][8][9][10][11][12][13][14][15][16] and convergent functional genomics (CFG) analysis. 17 These promising candidates include DISC1, [18][19][20] NRG1, [21][22][23] ZNF804A, 16,24,25 TCF4, 8,15,26 MIR137 6 and genes from the MHC region.…”
Section: Introductionmentioning
confidence: 99%
“…1 So far, numerous molecular genetic studies on schizophrenia have been performed, and many susceptibility genes have been identified through linkage analyses, 2,3 candidate gene association studies, 4,5 genome-wide association studies (GWAS) [6][7][8][9][10][11][12][13][14][15][16] and convergent functional genomics (CFG) analysis. 17 These promising candidates include DISC1, [18][19][20] NRG1, [21][22][23] ZNF804A, 16,24,25 TCF4, 8,15,26 MIR137 6 and genes from the MHC region. 14,15 Though significant progress has been made in the genetic dissection of schizophrenia, [6][7][8][9][10][11][12][13][14][15][16]26 the pathophysiology of schizophrenia is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been speculated that the immune system is involved in SCZ, so the finding that the genetic effects are enriched in the MHC region or even in regions outside the MHC that are also involved in acquired immunity is consistent with this hypothesis. After the first GWAS reporting on the MHC region, a total of 30 loci across the whole genome were reported to be associated with SCZ by 2013 [15][16][17][18][19][20][21][22][23][24][25] , including the genes for transcription factor 4 (TCF4), neurogranin (NRGN), and DPYD/MIR317 that are known to play crucial roles in brain development. Of these GWASs, only two used…”
Section: Common Variants Contributing To Sczmentioning
confidence: 99%